SEMI-AUTHOMATIC METHOD FOR DISTRIBUTION OF EGGS OF SUGARCANE BORER (Diatraea saccharalis) IN THE REARING CUPS - Sgrillo, Ricardo B.; Wiendl, Frederico M.; Tornisielo, Waldemar L. (REVISTA DE AGRICULTURA, 2015)
SEMI-AUTHOMATIC METHOD FOR DISTRIBUTION OF EGGS OF SUGARCANE BORER (Diatraea saccharalis) IN THE REARING CUPS